The impact of HOV and HOT lanes on congestion in the United States - Robert Poole (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper describes the evolution of high-occupancy vehicle lanes (HOV) and high-occupancy toll lanes (HOT) lanes in the United States. It evaluates their performance and analyses the impact on carpooling and public transport. The demographics of HOV and HOT lane users and the implications for equal access are also examined. The paper also proposes ways to apply lessons learned from the success of HOV and HOT lanes to the political challenges of road pricing.
Keywords: 330; Verkehrsstau; Share Economy; Nahverkehrspolitik; USA